Pembagian Dan Penerapan Handsanitizer Dalam Upaya Pencegahan Penyebaran Covid-19 Pada Masyarakat Kelurahan Aek Tampang - Diningsih, Ayus; Ritonga, Nefonavratilova (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
Hand sanitizer is an alcohol-based hand sanitizer product that can be in the form of a gel or liquid. Hand sanitizer can instantly kill germs without using water, can be used anytime and anywhere, for example after handling money, before eating and after eating. Hand sanitizer is an alternative to prevent the spread of the Covid-19 virus because it contains alcohol and other substances that can kill viruses that stick to the hands, especially in the area of ​​​​the hands. The form of hand sanitizer itself varies, ranging from gel, spray, to foam. The requirement for a hand sanitizer to be effective in killing germs and viruses is that it contains at least 60% alcohol. This community service program aims to distribute and implement hand washing with hand sanitizers in an effort to prevent covid-19 in the Aek Tampang village, South Padangsidimpuan District. The target of the outreach activities is the entire community in Environment III, Aek Tampang Village, South Padangsidimpuan District. The expected result of this service is that the community accepts and implements the use of Hand Sanitizer as a practical step for washing hands to prevent the spread of COVID-19.